Subjective risk for subject and rating preferences - Касьянов, Владимир Александрович (Eastern-European Journal of Enterprise Technologies, 2014)
The principle of maximum subjective entropy is presented in the paper. Two options of subjective risk are proposed, namely for subject alternatives and, subject preferences respectively, rating alternatives and, accordingly, rating preferences. In both cases, all subjective categories relate to a certain “individual carrier”: a set of alternatives, distribution of preferences, maximizing functionals. An additional assumption of the entropy space structure is introduced: entropy thresholds make the final area of changing the entropy on subareas so that the entropy transition from one area to another radically alters the behavior of the subject “decision maker.” Also, thresholds for subjective risks are introduced. The proposed theory can serve as a basis for improving the methods of active system management for self-government process analysis.